A guide to using team management systems (TMS) for learning and teaching quality improvement in health care teams. - O'Keefe, Maree; Stupans, Ieva; McAllister, Sue; Burgess, Teresa; LeCouteur, Amanda (Australian Learning and Teaching Council (ALTC), 2011)
This is a guide to using team management systems for learning and teaching quality improvement in health care teams. It emanates from a project that involved a pilot investigation of the utility of team management systems (TMS) to identify and build leadership capacity within health service clinical teams. Participating clinical team members completed a team management profile. This initial profiling of individual team member management preferences provided an understanding of the range of existing work preferences within the team around student learning, and facilitated clinical team quality improvement planning. Six months later the clinical team completed a linking leader profile. This second profiling activity guided teams in the assessment of improvements that have been made, the identification of additional changes to team functioning that are required, and strategies that may be effective in achieving these goals. Each profile activity included individual questionnaires, feedback and a facilitated workshop. The development, implementation and impact of quality improvement plans was evaluated at several points in time by questionnaire, interview and observation.